Las actividades lúdicas en el proceso enseñanza-aprendizaje. - Martínez Toaquiza, Sonia Carmen (2018)
The research project was developed with the purpose of supporting the value of the inclusion of playful strategies in the teaching-learning process. The research problem is based in the lack of active and participatory strategies that allow achieving better results in the educational process at the basic elementary education levels, since teachers mainly use the master class as a central methodological strategy, subtracting dynamism, participation and activity on the part of the students. To achieve the research objectives, a research methodology was used with a mixed, qualitative and quantitative approach that allows a broad description of the research problem, with the support of the statistical data collected for the analysis of the use of play activities at teaching process. -learning, using documentary bibliographic research that allows deepening knowledge of the contribution and benefit of play activities to the educational process and exploratory research, since the demographic situation and the social and cultural characteristics of the sector have not benefited from projects related to playful activities that allow to teacher to diversify their teaching strategies. The obtained results from the research process make it possible to demonstrate that play strategies represent a valuable educational tool, adaptable to any content, situation and age, generating spaces for social interaction and sharing among peers, improving their cognitive and social skills. The contributions of the research have allowed establishing the existing deficiencies in the institution, due to the fact that the benefits of the play strategies are being wasted, as well as the main limitations for their inclusion at educational process. At the end of the research it was possible to conclude that teachers recognize the contribution of play strategies at teaching-learning process; however they detail the limitations for its application, such as insufficient teaching staff, lack of space and materials for the application of these strategies.